Biomimetic Glucose Trigger‐Insulin Release System Based on Hydrogel Loading Bidentate β‐Cyclodextrin. (3rd July 2021) - Wang, Renqi; Tian, Yuhui; Wang, Jiankang; Song, Wenxuan; Cong, Yong; Wei, Xuebing; Mei, Yingwu; Miyatake, Hideyuki; Ito, Yoshihiro; Chen, Yong Mei
Abstract: Initiated by the specific binding between D‐glucose and biological receptors, the human body has a delicate metabolic system to regulate blood D‐glucose levels, but failing to release insulin would induce hyperglycemia or type I diabetes. While insulin delivery is an effective form of hyperglycemia therapy, the self‐regulated triggering of insulin release for on‐demand supplementation remains inadequate. Here, a biomimetic glucose trigger‐insulin release system, that is, a bidentate β‐cyclodextrin‐based hydrogel with preloaded insulin is presented; the dual self‐regulated system shows a specific D‐glucose response to realize accurate monitoring and simultaneous on‐demand trigger insulin release. The specific binding between D‐glucose and the bidentate β‐cyclodextrin induces the release of protons, causing macroscopic swelling of the hydrogel, subsequently triggering the on‐demand and long‐term supplementation of insulin. On the contrary, isomers of D‐glucose, such as D‐fructose and D‐galactose, cause shrinking of the hydrogel, and retard insulin release. In‐vivo studies in type I diabetic mice model ascertain that although the bidentate β‐CD hydrogel is preloaded with short‐activity insulin, it exerts long‐activity control of blood glucose level over 12 h. Abstract : A novel bidentate β‐cyclodextrin polyacrylamide hydrogel facilitates self‐regulated D‐glucose specific swelling and on‐demand insulin release. The dual smart performance of the biocompatible hydrogel is validated both in vitro and in vivo. Its high specificity to D‐glucose is verified amongst various D‐glucose isomers. The hydrogel preloaded short‐activity insulin exerts long lasting blood glucose control in mice with type I diabetes.